Distance Method, Fixed Plot and Point Sampling for Basal Area and Tree Count Estimations in Sal - Tiwari, K. P.; Parthasarathy, V. (Indian Forester, 1976)
An investigation with three different methods namely Distance method, Fixed plot and Point sampling method for the estimation of basal area and tree count was made in Sal (Snorea robusta) forests of Doon Valley. The population consisted of Sal trees of 20 cm dhh and above. In distance methods the distance upto 6th to 10th tree from a systematically selected sample point was taken as plot size as against 0.1 ha fixed plot size. The results show that 10th tree method and point sampling method are suitable for such moderately clustered populations.